Arctium lappa L. polysaccharide can regulate lipid metabolism in type 2 diabetic rats through the SREBP-1/SCD-1 axis. (August 2020) - Chen, Min; Xu, Jingge; Wang, Yan; Wang, Zhen; Guo, Lanping; Li, Xinpeng; Huang, Luqi
Abstract: In the analysis of risk factors of diabetes mellitus with coronary heart disease, dyslipidemia is the most important. Previous studies have found that Arctium lappa L. polysaccharide (ALP) can regulate lipid metabolism in type 1 diabetic rats, but it has not been studied in type 2 diabetes. In this study, the regulatory effect of ALP on lipid metabolism in type 2 diabetic rats was investigated by constructing a model of type 2 diabetes. The results of blood biochemical analysis showed that ALP effectively reduced the synthesis of triglycerides and cholesterol, and reduced the risk of atherosclerosis in diabetic rats. Histopathological observation (hematoxylin and eosin, Masson, Periodic Acid-Schiff and oil red O staining) showed that it also effectively regulated lipid metabolism in the liver of diabetic rats and inhibited the process of liver fibrosis. Immunohistochemistry and Western blot analysis showed that ALP regulated the expression of sterol regulatory element-binding protein-1 (SREBP-1) and stearoyl-CoA desaturase 1 (SCD-1) in the liver of diabetic rats. In conclusion, the results of this study demonstrate that ALP can effectively regulate lipid metabolism and reduce the risk of atherosclerosis in type 2 diabetic rats through the SREBP-1/SCD-1 axis. Graphical abstract: Image 1 Highlights: Arctium lappa L. polysaccharide has a good regulatory effect on lipid metabolism caused by type 2 diabetes. Arctium lappa L. polysaccharide can control lipid metabolism disorder by regulating SREBP-1/SCD-1 in liver. Arctium lappa L. polysaccharide is a potential regulator of lipid metabolism disorder caused by diabetes.